Comparison of Underground Coal Mining Methods Based on Life Cycle Assessment - Wu, Haoyuan; Yin, Zhiqiang; Zhang, Yuchen; Qi, Chao; Liu, Xian; Wang, Jianen (Frontiers in Earth Science, 2022)
Different mining methods have different levels of environmental impact when mining underground coal resources. To identify the mining method with the lowest environmental impact, a life cycle assessment (LCA) was carried out using Simapro 9.0.0 software for the different mining methods. The Ecoinvent v3 database was used to provide background data, and the results were calculated using the Eco-indicator99 method. The study results show that for a 20m coal column, respiratory inorganics is identified as the dominant impact category based on normalized results, followed by fossil fuels, carcinogens, and climate change. The contribution analysis indicates that electricity and coal mining is essential in contributing to these significant impact categories and should be of particular concern. According to the sensitivity analysis, reducing mining activities and increasing the efficiency of extraction and use are the primary responses to address environmental pollution, followed by reducing environmental pollution from electricity production and steel production. In addition, a summary comparison of the single scores of different mining methods shows that the environmental burden of pillarless mining is the lowest, and it is found that as the width of the coal pillar gradually increases, its Single score shows a trend of increasing and then decreasing. Therefore, the single score of non-pillar mining is the lowest compared to other mining methods and can be the optimal mining method. This research can provide a scientific basis for the selection of green mining and underground coal resources mining methods.